(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes graphemes in the derivational aspect, which can function in the status of the text. Information is also given about their semantic and semiotic nature, expressed meaning, semantic features. In addition, the first place in the article is not the history of the origin of graphemes, but the fact that they are studied as a means of communication between people, and even in some situations they come to the status of a text, which means that they have a derivational characteristic of the text.v